If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 2y + 2z = 7 Solving 5x + 2y + 2z = 7 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2y' to each side of the equation. 5x + 2y + -2y + 2z = 7 + -2y Combine like terms: 2y + -2y = 0 5x + 0 + 2z = 7 + -2y 5x + 2z = 7 + -2y Add '-2z' to each side of the equation. 5x + 2z + -2z = 7 + -2y + -2z Combine like terms: 2z + -2z = 0 5x + 0 = 7 + -2y + -2z 5x = 7 + -2y + -2z Divide each side by '5'. x = 1.4 + -0.4y + -0.4z Simplifying x = 1.4 + -0.4y + -0.4z
| 4(4x-8)-5=(x-3)+35 | | r+9.3=-0.5 | | (X+1)+(3x+1)+(x+1)=180 | | P(x)=-0.1x^5+3.8x^4+5000 | | 7-x=-2x-5 | | 0.4+1.5=2.2-15x | | 2n^2+2n-42=0 | | 5(3+5x)-1=89 | | 10-2a+4=32 | | 3=-4n+3n | | 2(j-3)=9(6-3j)+10j | | 9x^2+26x+17=0 | | 3p+6=2p+10 | | 20(y+2)=4y+5 | | 2j-6=54-27j+10j | | x-34=-14 | | 4X-30+X+20=180 | | 8x^3-60x^2+150x-854=0 | | x-27=-17 | | -27=-5(9a+6) | | 12+8r=6-10r | | 10x+3(4x-2)=6 | | 7y+3(y-6)=6(y+1)-3 | | 12x-(8x-9)=45 | | 6x-7x+2=12 | | 2x-8+10=3x-7 | | 5*sin(14x)=5*cos(7x) | | 13x^2-8x-20=0 | | -2y+9x=3 | | -14+74=-5(x+3) | | 3y^2-4=y | | 2(4z+2)-6=70 |